The Value of Extra-lung Lesions on 18F-FDG PET/CT in Improving Diagnosis of Lung Cancer - Baoming MI; Weixing WAN; Chunjing YU; Xuyang YOU; Feng JIANG; Qingjun YOU (Chinese Journal of Lung Cancer, 2012)
Background and objective 18F-FDG PET/CT has several shortcomings in discriminating between lung carcinoma and pulmonary benign lesions. The aims of the present study is to explore the value of extra-lung lesions on 18F-FDG PET/CT image in the diagnosis of lung cancer. Methods A total of 126 suspected lung cancer patients underwent 18F-FDG PET/CT scan. Preliminary diagnoses were based on the PET characteristics, SUVmean value, and CT characteristics of the lesions in the lung, and the diagnoses were modified based on the detected extra-lung lesions. The difference between the two methods and their disparity were calculated. Results Extra-lung lesions were identified on the PET/CT image in 81 patients; extra-lung metastasis modified 13 probable malignancies to affirmative malignancy and 1 probable malignancy to benign lesion. Non-metastasis modified 2 probable malignancies to affirmative malignancy and 1 probable malignancy to benign lesion. Fifteen were correct, whereas 2 were misdiagnosed. The diagnoses modification rate was 13.5% (17/126), and the modified diagnoses accuracy is 88.2% (15/17). Conclusion Extra-lung lesions demonstrated on 18F-FDG PET/CT improved the diagnostic accuracy of lung cancer. Tuberculosis was identified as the most important reason for false positive diagnoses after modification by extra-lung lesions.